Pentingnya pendidikan Pancasila bagi jenjang sekolah dasar - Ita'ufaidilah, Salvi (Maliki Interdisciplinary Journal, 2024)
Pancasila is the result of the Indonesian people’s own thoughts or deepest thoughts and is believed, trusted and considered by the Indonesian people as the best, wisest, fairest, most honest and most appropriate. In the era of globalization, the value of Pancasila is increasingly deteriorating due to the presence of many foreign cultures that are popular among Indonesian people. Therefore, we must find a way to preserve the ideology of this country. This research uses a literature review method. The literature review research method is a research method that involves reading and analyzing literature related to the topic being discussed. Maintaining Pancasila can be achieved by teaching Pancasila training to elementary school children according to their level. Elementary school age children have the ability to think concretely and logically, thus enabling them to carry out learning. Therefore, by teaching Pancasila values to children in elementary school, these memories can be maintained and developed so that they can give birth to a good generation in the future.